Examining Sustainability Factors for Organizations that Adopted Stanford’s Chronic Disease Self-Management Program - Tomioka, Michiyo; Braun, Kathryn L. (Frontiers in Public Health, 2015)
In 2006, funds were received to replicate Stanford’s Chronic Disease Self-Management Program (CDSMP) among eldercare providers in Honolulu. This case study, conducted 1 year after the close of the initial 3-year replication grant, explored factors for sustaining the delivery of CDSMP, with an aim to create guidelines for cultivating sustainability. Face-to-face semi-structured interviews were conducted with one representative from each of eight eldercare agencies, with the representative specified by the agency. Representatives discussed the presence and strength (low, medium, or high) of sustainability factors, including readiness, champions, technical assistance, perceived fit of CDSMP with their agency, CDSMP modifiability, perceived benefits of CDSMP, and other. Only three of the eight agencies (38%) were still offering CDSMP by the end of 2010. Agencies who sustained CDSMP rated higher on all sustainability factors compared to those that did not sustain the program. Additional factors identified by representatives as important were funding and ongoing access to pools of elders from which to recruit program participants. When replicating evidence-based programs, sustainability factors must be consciously nurtured. For example, readiness must be cultivated, multiple champions must be developed, agencies must be helped to modify the program to best fit their clientele, evaluation findings demonstrating program benefit should be shared, and linkages to funding may be needed.